The Impact of Organizational Culture, Digital Literacy, and Work Ethic on Lecturers’ Work Commitment in University - Wardah Wardah; Marwan Mawarn; Najmuddin Najmuddin (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The commitment of lecturers is crucial for maintaining the sustainability and quality of higher education institutions, especially due to a rapid development in technology and escalating worldwide competition. This study aims to analyse the impact of organizational culture, digital literacy, and work ethic on lecturers' commitment to their work in universities in Langsa City. A quantitative study design utilizing a survey methodology was implemented. Data were gathered from 120 instructors at Universitas Cut Nyak Dhien employing structured questionnaires. The data were examined by multiple linear regression analysis. The findings demonstrate that organizational culture exerts a favourable and significant influence on lecturers' work dedication. Digital literacy presents a substantial and major impact on work commitment, whereas work ethic positively and significantly enhances lecturers' commitment. Organizational culture, digital literacy, and work ethic concurrently influence lecturers' dedication to their work. The findings underscore the necessity of fortifying organizational culture, augmenting digital literacy skills, and cultivating a robust work ethic as strategic initiatives to enhance lecturers' commitment at higher education institutions.